Strategi Komunikasi dan Sosialisasi Pembuatan Eco Enzyme Sebagai Upaya Pengolahan Limbah Organik - Shafrani, Kharisma; Darmaningrum, Khaerunnisa Tri (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
Pacar Village is strategically located along the coastal route and close to government offices in Tirto Sub-district, so many residents of Pacar Village sell food around these offices. One of the problems faced is the problem of waste, especially with the increasing production of organic and inorganic waste due to the large number of food vendors in Pacar Village. This article aims to understand how the Pacar Village government can process organic waste into eco enzyme. It is hoped that this article can help the community implement waste management efforts into useful products and assist the government in environmental conservation and waste management strategies. The article method used is descriptive with a qualitative approach. The subject of the article is the community of Pacar Village, Tirto Subdistrict, and data were collected through observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and data conclusion. The results of the article show that organic waste in Pacar Village can be processed into eco enzyme which can be used as liquid fertilizer, soap, and hand sanitizer. The strategy of making eco enzyme to manage organic waste has been successful,turning the accumulated organic waste into products of economic value and usefulness.